Kepatuhan Berkelanjutan Sertifikasi Halal: Kajian Sistematis Audit Internal, CAPA, dan Tinjauan Manajemen - Kesuma, Maryanda Warta; Saputra, Sandri; Rifai, Ahmad; Somantri, Ace (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Sustainable halal compliance cannot be demonstrated solely through the possession of halal certification; rather, it is determined by the effectiveness of internal control performance within the Halal Product Assurance System (HPAS). This article presents a systematic literature review to synthesize empirical evidence on the roles of internal audits, Corrective and Preventive Actions (CAPA), and management review in shaping sustainable compliance as an outcome of a management system. The review follows PRISMA principles through a structured keyword search linking HPAS/halal assurance systems (including HAS 23000) with internal audit, nonconformity, corrective action/CAPA, management review, and the PDCA cycle. The selected literature covers studies on halal certification implementation, halal governance, and related management systems across various contexts, including micro, small, and medium enterprises (MSMEs) and halal supply chains. Thematic synthesis indicates that internal audits function as mechanisms for detection and organizational learning, CAPA operates as a recovery and prevention mechanism that ensures effective closure of nonconformities, and management review transforms compliance data into strategic decisions guiding risk prioritization, resource allocation, and system improvement. Based on these findings, this article proposes a “Halal Compliance Loop” framework grounded in the PDCA cycle and recommends practical performance indicators, such as the recurrence of nonconformities, timeliness of corrective action closure, and the implementation rate of management review decisions. Future research is encouraged to examine the effectiveness of internal control mechanisms within HPAS across different organizational scales and to explore the integration of halal controls with other management systems and digital traceability technologies.